rac-1-Acetyl-5-benzyl-2-thioxoimidazolidin-4-one - Uzcátegui, Mary C. (International Union of Crystallography, 2008)
In the title compound, C(12)H(12)N(2)O(2)S, the molecules have a wing-like conformation, with a distance of 3.797 (2) Å between the centroids of the five- and six-membered rings. In the crystal structure, molecules are linked by N—H⋯O hydrogen bonds, forming infinite one-dimensional zigzag chains, running along [001], with a C(4) graph-set motif.